2018
DOI: 10.2341/17-124-c
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Study of Zirconia Full-coverage Restorations on Teeth Prepared With Biologically Oriented Preparation Technique on Gingival Health: Results After Two-year Follow-up

Abstract: Two years after treatment, vertical preparation without finish line produces gingival thickening, margin stability, and optimal esthetics. Neither crowns nor FPDs presented any mechanical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 12 publications
1
46
0
4
Order By: Relevance
“…The clinical experience of BOPT reported in the literature has established that this technique increases the thickness of gingival tissue and enhances the stability of the soft tissue in the mediumand long-term compared to other classical preparations with finishing lines [5,7,8] (Figures 16-20). hence, the conclusions of this technique are based on methods that are imprecise and subjective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical experience of BOPT reported in the literature has established that this technique increases the thickness of gingival tissue and enhances the stability of the soft tissue in the mediumand long-term compared to other classical preparations with finishing lines [5,7,8] (Figures 16-20). hence, the conclusions of this technique are based on methods that are imprecise and subjective.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for the manufacture of the provisional prosthesis is of key significance as it determines the new emergence context, placing it at different levels within the gingival sulcus. This allows the surrounding soft tissue to adjust its form and position to accommodate the new prosthetic profile, thereby guiding the healing, the reinsertion, and the thickening of the gingival tissue [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tooth reduced by BOPT does not have a finish line (nor is it a knife-edge finish line), as the finish line is defined by the edge of the prosthetic restoration and is characterized by contouring the crown in the cervical area in relation to periodontal parameters. Although BOPT is a fairly recent development, several short-medium term prospective studies have reported good perio-prosthetic clinical behavior, observing stability of the gingival margin, and increased gingival thickness in the area of prosthetic emergence, which is the main factor of concern to restorative dentists ( 3 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted to date vouches for good periodontal behavior around teeth prepared by BOPT, and for the stability of peri-coronal soft tissues ( 3 ). In BOPT, both the tooth and the gingiva are drilled, creating an axial plane by means of vertical tooth reduction.…”
Section: Introductionmentioning
confidence: 99%